AMECM/DCB scaffold prompts successful total meniscus reconstruction in a rabbit total meniscectomy model. (December 2016) - Yuan, Zhiguo; Liu, Shuyun; Hao, Chunxiang; Guo, Weimin; Gao, Shuang; Wang, Mingjie; Chen, Mingxue; Sun, Zhen; Xu, Yichi; Wang, Yu; Peng, Jiang; Yuan, Mei; et al.
Abstract: Tissue-engineered meniscus regeneration is a very promising treatment strategy for meniscus lesions. However, generating the scaffold presents a huge challenge for meniscus engineering as this has to meet particular biomechanical and biocompatibility requirements. In this study, we utilized acellular meniscus extracellular matrix (AMECM) and demineralized cancellous bone (DCB) to construct three different types of three-dimensional porous meniscus scaffold: AMECM, DCB, and AMECM/DCB, respectively. We tested the scaffolds' physicochemical characteristics and observed their interactions with meniscus fibrochondrocytes to evaluate their cytocompatibility. We implanted the three different types of scaffold into the medial knee menisci of New Zealand rabbits that had undergone total meniscectomy; negative control rabbits received no implants. The reconstructed menisci and corresponding femoral condyle and tibial plateau cartilage were all evaluated at 3 and 6 months (n = 8). The in vitro study demonstrated that the AMECM/DCB scaffold had the most suitable biomechanical properties, as this produced the greatest compressive and tensile strength scores. The AMECM/DCB and AMECM scaffolds facilitated fibrochondrocyte proliferation and the secretion of collagen and glycosaminoglycans (GAGs) more effectively than did the DCB scaffold. The in vivo experiments demonstrated that both the AMECM/DCB and DCB groups had generated neomeniscus at both 3 and 6 months post-implantation, but there was no obvious meniscus regeneration in the AMECM or control groups, so the neomeniscus analysis could not perform on AMECM and control group. At both 3 and 6 months, histological scores were better for regenerated menisci in the AMECM/DCB than in the DCB group, and significantly better for articular cartilage in the AMECM/DCB group compared with the other three groups. Knee MRI scores (Whole-Organ Magnetic Resonance Imaging Scores (WORMS)) were better in the AMECM/DCB group than in the other three groups at both 3 and 6 months. At both 3 and 6 months, RT-PCR demonstrated that aggrecan, Sox9, and collagen II content was significantly higher, and mechanical testing demonstrated greater tensile strength, in the AMECM/DCB group neomenisci compared with the DCB group.